2021
DOI: 10.1038/s41598-021-86083-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide is associated with stroke

Abstract: We aimed to determine if plasma levels of bacterial lipopolysaccharide (LPS) and lipoteichoic acid (LTA) are associated with different causes of stroke and correlate with C-reactive protein (CRP), LPS-binding protein (LBP), and the NIH stroke scale (NIHSS). Ischemic stroke (cardioembolic (CE), large artery atherosclerosis (LAA), small vessel occlusion (SVO)), intracerebral hemorrhage (ICH), transient ischemic attack (TIA) and control subjects were compared (n = 205). Plasma LPS, LTA, CRP, and LBP levels were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Among the 10 genes mentioned above, the increase in expression of Lbp (lipopolysaccharide binding protein), Cd14 (CD14 molecule), and Lgals3 (galectin 3) is likely related to an activation of microglial cells through Tlrs. An initiation of the Tlr signaling can occur through transfer of bacterial LPS, particularly as plasma levels of LPS are elevated in ischemic stroke [ 5 , 28 ], by Lbp to a receptor complex that localizes on microglia and includes Tlrs (the most known Tlr4) and co-receptor CD14. Expression of another gene, Lgals3 , was related to microglial activation in experimental ischemia in gerbils [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 10 genes mentioned above, the increase in expression of Lbp (lipopolysaccharide binding protein), Cd14 (CD14 molecule), and Lgals3 (galectin 3) is likely related to an activation of microglial cells through Tlrs. An initiation of the Tlr signaling can occur through transfer of bacterial LPS, particularly as plasma levels of LPS are elevated in ischemic stroke [ 5 , 28 ], by Lbp to a receptor complex that localizes on microglia and includes Tlrs (the most known Tlr4) and co-receptor CD14. Expression of another gene, Lgals3 , was related to microglial activation in experimental ischemia in gerbils [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is also associated with increases of cytokines, chemokines, lipopolysaccharide (Hakoupian et al, 2021), inflammation and increased oxidative stress that contribute to white matter injury (Altendahl et al, 2020). Indeed, T cell infiltration of white matter is associated with cognitive decline as normal monkeys age (Batterman et al, 2021).…”
Section: Multiple Mechanisms Of White Matter (Wm) Injury In Ad Agementioning
confidence: 99%
“…CRP is a plasma acute-phase protein whose concentrations increase in response to inflammation. Our recent study has demonstrated that plasma LPS levels positively correlated with plasma CRP levels in humans (Hakoupian et al, 2021 ). Other studies demonstrated that CRP levels are elevated in blood years before the onset of AD (Schmidt et al, 2002 ; Engelhart et al, 2004 ), and plasma CRP levels are higher in patients with AD compared to controls (Song et al, 2015 ).…”
Section: Discussionmentioning
confidence: 93%
“…Lipopolysaccharides are the major components of the outer membrane of Gram-negative bacteria and are potent inflammatory agents. LPS has been identified in human blood (Klimiec et al, 2016(Klimiec et al, , 2018Hakoupian et al, 2021) and brains (Zhan et al, 2016(Zhan et al, , 2018 with higher levels of LPS in blood (Zhang et al, 2009) and brains (Zhan et al, 2016(Zhan et al, , 2018Zhao et al, 2017) of AD compared to controls. CRP is a plasma acute-phase protein whose concentrations increase in response to inflammation.…”
Section: Inflammation Of Pvwm In Ad and Aging Brainsmentioning
confidence: 99%